Activation of two dopants, Bi and Er in δ-doped layer in Si crystal. Issue 4 (4th January 2022) - Murata, Koichi; Yagi, Shuhei; Kanazawa, Takashi; Tsubomatsu, Satoshi; Kirkham, Christopher; Nittoh, Koh-ichi; Bowler, David R; Miki, Kazushi
Abstract: Conventional doping processes are no longer viable for realizing extreme structures, such as a δ -doped layer with multiple elements, such as the heavy Bi, within the silicon crystal. Here, we demonstrate the formation of (Bi + Er)- δ -doped layer based on surface nanostructures, i.e. Bi nanolines, as the dopant source by molecular beam epitaxy. The concentration of both Er and Bi dopants is controlled by adjusting the amount of deposited Er atoms, the growth temperature during Si capping and surfactant techniques. Subsequent post-annealing processing is essential in this doping technique to obtain activated dopants in the δ -doped layer. Electric transport measurement and photoluminescence study revealed that both Bi and Er dopants were activated after post-annealing at moderate temperature.